Implementasi Pembelajaran Akidah Akhlak Dalam Meningkatkan Pembentukan Akhlak Siswa Kelas IV di MI Ar-Rizqi - Mahpudin, Pupu; Alfarisi, Aris Salman (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2025)
The objectives of this study were to determine: 1.) To find out the planning of the implementation of Akidah akhlak learning in improving the moral formation of students at MI Ar-Rizqi Gubug, Sajira District; 2.) To find out the implementation of Akidah Akhlak learning in improving the moral formation of students at MI Ar-Rizqi Gubug, Sajira sub-district; 3.) To find out the evaluation of Akidah Akhlak learning in improving students' moral formation at MI Ar-Rizqi Gubug, Sajira sub-district. This research was conducted using descriptive qualitative research and for data collection techniques using observation, interview and documentation methods. Data were analyzed by data reduction, data presentation, and conclusion drawing. The results of this study are as follows: 1.) Lesson planning has been made by teachers long before the learning process at the beginning of the semester takes place, and researchers discuss existing lesson plans and what will be taught to children. 2.) In the implementation of learning in the classroom the teacher is in accordance with the 2013 Curriculum starting from the introduction, core activities to the closing. In the learning implementation strategy, the teacher uses the lecture method too much and is still very dominant in the learning process carried out. Likewise, with the use of media, Akidah Akhlak teachers adjust the appropriate media to the material to be studied, although Mi Ar Rizqi still lacks facilities and facilities that support K13 learning. 3.) Evaluation of Akidah Akhlak learning such as conducting several written and oral tests, conducting daily assessments and others.